Correlation coefficients of three self-perceived orthodontic treatment need indices - Faezeh Eslamipour; Farnaz Tajmir Riahi; Milad Etemadi; Alireza Riahi (Wolters Kluwer Medknow Publications, 2017)
Background: To determine patient orthodontic treatment need, appropriate self-perceived indices are required. The aim of this study was to assess the sensitivity and specificity of esthetic component (AC) of the index of orthodontic treatment need (IOTN), oral esthetic subjective index scale (OASIS), and visual analog scale (VAS) through dental health component (DHC) IOTN as a normative index to determine the more appropriate self-perceived index among young adults. Materials and Methods: In this cross-sectional study, a sample of 993 was randomly selected from freshman students of Isfahan University. Those with a history of orthodontic treatment or current treatment were excluded. DHC was evaluated by two inter- and intra-calibrated examiners. Data for AC, OASIS, and VAS were collected through a questionnaire completed by students. Descriptive statistics, Mann-Whitney U-test, and Spearman correlation test, were used for data analyses. Sensitivity, specificity, positive and negative predictive values of self-perceived indices were calculated through DHC. Results: Sensitivity of AC, OASIS, and VAS for evaluating definite orthodontic treatment need was calculated at 15.4%, 22.3%, and 44.6%, respectively. Specificity of these indices for evaluating definite orthodontic treatment need was calculated at 92.7%, 90.5%, and 76.2% percent, respectively. All self-perceived indices had a significant correlation with together and with DHC (P < 0.01). Among demographic factors, there was weak but significant correlation only between mother's educational level and VAS (P < 0.01). Conclusion: Due to the sensitivity and specificity of the three self-perceived indices, these indices are not recommended for population screening and should be used as adjuncts to a normative index for decision-making in orthodontic treatment planning.